CARDIOVASCULAR RISK FACTORS, LIFESTYLE AND SOCIAL DETERMINANTS IN A CROSS-SECTIONAL POPULATION STUDY- LAPARC STUDY. (April 2021) - Leiria, Vinicius; Muxfeldt, Elizabeth Silaid; Pecly, Inah Maria Drummond; Botelho, Bruna Gopp; Barbalho, Daniella Gomes; Mourão, Maria Antonia Oakim
Abstract: Objective: To evaluate the relationship between the main CV risk factors and socioeconomic indicators in a population of adults registered in a Family Health Care (FHC) unit in the center of Rio de Janeiro. Design and method: Cross-sectional population study that included adults aged between 20 and 50 years living in the area covered by the FHC in Rio de Janeiro. Demographic data (gender and age), socioeconomic data (education level, profession, employment), CV risk factors (smoking, sedentary lifestyle, obesity, hypertension, diabetes, dyslipidemia) were recorded. The metabolic profile is evaluated through laboratory tests. Those who studied up to high school were considered poorly educated. Results: 604 individuals were enrolled [39% male, mean age: 38.8 ± 8, 9 years] The median of schooling was 12 years. 288 individuals had high schooling, 44.5% were male. A total of 130 individuals did not study or work. Women with low education had a higher risk of smoking, obesity and hypertension with no difference regarding labor or study activities. Otherwise, men with low education had higher risk of sedentary lifestyle and hypertension. Among men, not working or studying increased the risk of smoking and hypertension. Conclusions: We found an inverse association between socioeconomic conditions and the prevalence of CV risk factors. Women are more affected by low schooling, while men are more affected by their working occupation. The study suggests that socioeconomic factors influence the CV risk, affecting men and women differently, pointing to the need for public policies to reverse this situation.